The Regional Greenhouse Gas Initiative: What It Means for Maine - Bogdonoff, Sondra (Maine Policy Review, 2008)
The federal government has been slow to act on curbing greenhouse gas emissions that contribute to climate change and on reducing dependence on petroleum and other fossil fuels. In the absence of federal leadership, Maine and other states have enacted policies and practices to try to address these issues. Sondra Bogdonoff’s article discusses the 10-state Regional Greenhouse Gas Initiative (RGGI), in which Maine participates, the first regional program in the U.S. to address climate change. RGGI is a cap-and-trade system aimed at reducing CO2 emissions, which are “capped” at allowable levels. Power generators can buy and sell allowances. Under RGGI, each state must sell or auction off 25 percent of its allowances and use the proceeds to promote energy efficiency or new clean energy technologies
Keywords: Northeast U.S.; Regional Greenhouse Gas Initiative; RGGI; cap and trade